1999
DOI: 10.1149/1.1390775
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Etching in HNO[sub 3]/HF Solution: Charge Balance for the Oxidation Reaction

Abstract: The potential dependence of the current and the etch rate of p-and n-type silicon electrodes in 6 M HNO 3 -6 M HF solution was investigated. Hydrogen evolved during etching at the open-circuit potential was also measured. These results give insight into the different processes occurring during etching. A detailed charge balance for silicon oxidation in the etchant is deduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 20 publications
3
76
0
1
Order By: Relevance
“…31,32 In both cases, increasing the H 2 O 2 or HF concentration increases the oxidation rate and dissolution rate, respectively, resulting in nanostructures with varying optical properties. 33 Figures 1(a) to 1(h) show the crosssection SEM micrographs and TEM images acquired from the NW samples grown with HF concentration of 1.8 M, 2.8 M, 4.8 M, and 5.8 M in a fixed H 2 O 2 concentration of 0.5 M. From Fig.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 In both cases, increasing the H 2 O 2 or HF concentration increases the oxidation rate and dissolution rate, respectively, resulting in nanostructures with varying optical properties. 33 Figures 1(a) to 1(h) show the crosssection SEM micrographs and TEM images acquired from the NW samples grown with HF concentration of 1.8 M, 2.8 M, 4.8 M, and 5.8 M in a fixed H 2 O 2 concentration of 0.5 M. From Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2), experimental data have shown that standard deviation of the depth of isolation grooves is almost constant in the p-type Si region indicating a low etching rate. However, the etching rate is strongly dependent on carrier concentration [12] which varies by four orders of magnitude in the p-type region of high-power Si devices under consideration [13]. It is reasonable to assume that hydrogen atoms, which have originated as the reaction products, penetrate into Si during etching process and passivate dopant boron atoms leading to a formation of a high-resistivity layer.…”
Section: Resultsmentioning
confidence: 99%
“…However, several further species including NO2, N2O, and H2 were detected as additional reaction products of HF-HNO3-H2O etching solutions [6,7], and the formation of an intermediate silicon dioxide layer was excluded by means of XPS measurements [8,9]. Instead, after etching in HF-containing solutions silicon surfaces are completely hydrogen-terminated, and in a few cases F atoms have been detected on the silicon surface.…”
Section: Introductionmentioning
confidence: 98%